Design of E-Learning Media Modules Based on FlipBook Maker Pro in Basic Computer Networking Subjects at SMKN 1 Tanjung Raya Even Semester Academic Year 2021/2022 - Radyuli, Popi; Menrisal; Diati, Lili Safitri (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2022)
This research and design aims to produce an E-Module based on FlipBook Maker Pro for class X TKJ students at SMK Negeri 1 Tanjung Raya. This study uses research and development methods (Research & Development). The design of this study used the model (ADDIE). By design the development steps are as follows (1) Analyze, (2) Design, (3) Development, (4) Implementation (5) Evaluate. The results of the validity test by the experts as a whole amounted to 86.85%, so that the level of validity can be interpreted as valid to use. The result of the overall practicality test assessment is 82.83%, so that the practicality level can be interpreted as practical to use. The results of the assessment of the overall effectiveness of the test items are 85.57%, so that the level of effectiveness can be interpreted as being effectively used. In conclusion, based on the assessment along with expert input and the results of the field trial, the E-Module based on FlipBook Maker Pro has been tested to be valid, practical and also effective in being used in the learning process on Basic Network Computer subjects for class X TKJ at SMKN 1 Tanjung Raya.